2015
DOI: 10.1007/s13762-015-0808-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of soil heavy metals in different land uses of an industrial area of Tehran (Iran)

Abstract: Vegetation and different land uses may affect the spatial distribution of heavy metals in soils. The objective of the current article was to study the impact of industrial activities and land use type on the distribution of heavy metals in soils of Chitgar Forrest Park, located in industrial zone in the west of Tehran City. The soil samples were taken from 116 sites in a regular sampling grid (250 9 250 m) at a depth of 0-20 cm, including three different land uses, needle leaf forests, broadleaf forests and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
17
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 59 publications
11
17
2
Order By: Relevance
“…However, Reza et al [39] while working on alluvial soils of India describes Spherical model to be the best fit for N, P and Zn contents. Moreover the findings are consistent with the researches of Some'e et al [40] and Mahmoudabadi et al [41].…”
Section: Analysis Of Spatial Dependence Of Soil Fertility Parameterssupporting
confidence: 92%
“…However, Reza et al [39] while working on alluvial soils of India describes Spherical model to be the best fit for N, P and Zn contents. Moreover the findings are consistent with the researches of Some'e et al [40] and Mahmoudabadi et al [41].…”
Section: Analysis Of Spatial Dependence Of Soil Fertility Parameterssupporting
confidence: 92%
“…As in our study, earlier works observed significant positive correlations of soil organic carbon with exchangeable metals (Behera & Shukla, ; Kargar et al ., ; Mahmoudabadi et al ., ). This was observed in total elements as well.…”
Section: Resultsmentioning
confidence: 92%
“…It is often assumed that pH is the most important variable controlling the bioavailability of metals; however, TOC (as observed in this work), organic matter, aluminum and iron oxides, cation exchange capacity, and soil texture also influence the availability of exchangeable metals (Arenas‐Lago et al ., ; Chavez et al ., ). The content of heavy metals is often high in clay‐rich soils comparing to silty or sandy soils that have had similar metals exposures (Esmaeili et al ., ; Mahmoudabadi et al ., ). Clay‐rich soils have a high capacity to retain heavy metals compared to sandy soils because they have a high cation exchange capacity comparing to soils with coarser textures (Chang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Different geographical factors, especially land use patterns, have various effects on the accumulation of metal elements [57][58][59][60][61]. The soil metals in the study area have different degrees of accumulation under various land use patterns, elevations, soil types, and slopes, but the cumulative characteristics are generally consistent (Figure 9).…”
Section: Factors Affecting the Distribution Of The Metal Contentmentioning
confidence: 85%